Algorithm of optimal technology selection of broadband access network - S. Sadchikova; M. Abdujapparova; D. Normatova (Universitas Ahmad Dahlan, 2019)
High speed applications require the access network upgrading based on new optical technologies in “last mile”. At the planning stage of network modernization, special algorithms and techniques allow optimize and automate the designing process of network upgrade based on copper cables. However, these techniques are completely inapplicable if optical technologies are used to the access network modernization. Designed algorithm simplifies the throughput calculation of current access nodes and planning of new access nodes depending on subscriber’s requirementstto the broadband services. Developed program based on proposed algorithm allows to determinate access nodes optimal deployment as well as the required equipment characteristics.